A 254-276 GHz On-Chip THz Antenna Using Substrate Integrated Waveguide and Metamaterials for Short-Range Wireless Communications - Paudel, Biswash; Li, Jack; Seet, Boon-Chong (IEEE Region 10 (Asia Pacific), 2023)
This paper presents a novel, low-profile on-chip antenna (OCA) based on metamaterials (MTM) and substrate-integrated waveguides (SIW), operating in the frequency range of 254–276 GHz. It consists of five stacked layers: copper patch, polyimide, copper ground, polyimide, and a copper microstrip feedline. The top copper layer consists of a 2×2 array of square patches with sub-wavelength-sized cross-sectional slots, which modify the array into a metamaterial. The antenna is excited by aperture coupling through the slot present in the ground layer. Both the top and bottom substrate layers are encapsulated by a series of metallic vias on either side. The proposed OCA is 500×500 × 130 µm 3 in size. Simulation results using Ansys High Frequency Structure Simulator (HFSS) indicate that the proposed OCA is promising for the integrated wireless system for short-range communications.